Multiwalled Carbon Nanotube and Poly(Brilliant Cresyl Blue)‐Ternary Deep Eutectic Solvent‐Modified Electrodes for Simultaneous Determination of Acetaminophen and Dopamine - Liang, Xizhen; Xinyi, Liu; Yueming, Zhou; Brett, Christopher M. A. (Electroanalysis (New York, N.Y.), 2025)
An electrochemical platform based on multiwalled carbon nanotubes (CNT) and poly(brilliant cresyl blue) (PBCB) modified glassy carbon electrodes has been fabricated with electropolymerization in ternary deep eutectic solvents (DES). The DES are composed of choline chloride as hydrogen bond acceptor and ethylene glycol and fructose as hydrogen bond donors, the proportions of which were optimized. Characterization was carried out by cyclic voltammetry, electrochemical impedance spectroscopy, and scanning electron microscopy. The performance of the modified electrode as sensor was evaluated for simultaneous detection of dopamine (DA) and acetaminophen (APAP) in Britton–Robinson buffer aqueous solution by differential pulse voltammetry. The combination of CNT and PBCB formed in DES led to a synergistic effect resulting in improved electrochemical sensor performance. The electrochemical platform was successfully used for the simultaneous determination of APAP in pharmaceutical samples and of DA and APAP in human saliva and urine, with good recoveries. Polymer film ternary DES PBCB/CNT/GCE sensor for determination of dopamine and acetaminophen in pharmaceuticals, human saliva or urine.